The Role of Teachers in Implementing Responsibility Characters in Grade IV Students at SD Negeri Kedungboto - Eka Sri Astutik; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2020)
This study discusses the role of the teacher in implementing the character of responsibility in fourth grade students at SDN Kedungboto-Porong. The focus of this research leads to the fourth grade teachers about the role of the teacher in implementing the character of responsibility in SDN Kedungboto. This research uses qualitative research. Type of descriptive qualitative research. This study uses the collection techniques used, namely observation, interviews and documentation. Data analysis techniques used to describe the results of interviews of research subjects, taken from the results of observation. The results showed the teacher's role in implementing the character of responsibility in grade IV students at Kedungboto-Porong Elementary School were teachers as educators, teachers as instructors, teachers as tutors, teachers as models and role models, teachers as models and role models, teachers as assessors. While the supporting factors of teachers in implementing the character of responsibility in grade IV students at SDN Kedungboto-Porong are the cohesiveness of the school principal and the teacher, as well as the role of the parents, the students' awareness. The inhibiting factor is the low parental control, affecting the community environment. The teacher in implementing the character of responsibility has been very approved, involving several students who still have bad character. However, there are more students who have good character.